Costs and quality of life in a randomized trial comparing minimally invasive and open distal pancreatectomy (LEOPARD trial). Issue 7 (23rd April 2019) - van Hilst, J; Strating, E A; de Rooij, T; Daams, F; Festen, S; Groot Koerkamp, B; Klaase, J M; Luyer, M; Dijkgraaf, M G; Besselink, M G; van Santvoort, H C; de Boer, M T; et al.
Abstract: Background: Minimally invasive distal pancreatectomy decreases time to functional recovery compared with open distal pancreatectomy, but the cost-effectiveness and impact on disease-specific quality of life have yet to be established. Methods: The LEOPARD trial randomized patients to minimally invasive (robot-assisted or laparoscopic) or open distal pancreatectomy in 14 Dutch centres between April 2015 and March 2017. Use of hospital healthcare resources, complications and disease-specific quality of life were recorded up to 1 year after surgery. Unit costs of hospital healthcare resources were determined, and cost-effectiveness and cost–utility analyses were performed. Primary outcomes were the costs per day earlier functional recovery and per quality-adjusted life-year. Results: All 104 patients who had a distal pancreatectomy (48 minimally invasive and 56 open) in the trial were included in this study. Patients who underwent a robot-assisted procedure were excluded from the cost analysis. Total medical costs were comparable after laparoscopic and open distal pancreatectomy (mean difference €–427 (95 per cent bias-corrected and accelerated confidence interval €–4700 to 3613; P = 0·839). Laparoscopic distal pancreatectomy was shown to have a probability of at least 0·566 of being more cost-effective than the open approach at a willingness-to-pay threshold of €0 per day of earlier recovery, and a probability of 0·676 per additional quality-adjusted life-year at a willingness-to-pay threshold of €80 000. There were no significant differences in cosmetic satisfaction scores (median 9 (i.q.r. 5·75–10) versus 7 (4–8·75); P = 0·056) and disease-specific quality of life after minimally invasive (laparoscopic and robot-assisted procedures) versus open distal pancreatectomy. Conclusion: Laparoscopic distal pancreatectomy was at least as cost-effective as open distal pancreatectomy in terms of time to functional recovery and quality-adjusted life-years. Cosmesis and quality of life were similar in the two groups 1 year after surgery. Graphical Abstract: Laparoscopic distal pancreatectomy decreases time to functional recovery compared with open distal pancreatectomy, but the cost-effectiveness has yet to be established. A cost-effectiveness study was performed showing that laparoscopic distal pancreatectomy was at least as cost-effective as the open approach in terms of time to functional recovery and quality-adjusted life-years. Similar cost utility and quality of life